High fidelity influence analysis of material and structure on sealing characteristics of aviation pipeline fittings based on multi-scale model - Shuai Zhao; Qiang Zhang; Rongrong Zhao; Yangyang Yan; Feng Li; Hongmei Wei (Scientific Reports)
Abstract As an important component connecting and sealing the high-pressure fluid in the hydraulic pipeline, the reliability and stability of the aviation pipeline fittings are critical. The purpose of this paper is to better understand and analyze the multiple parameters influence on sealing characteristics of aviation pipeline fittings. This article significantly improves the accuracy of sealing contact state analysis based on multi-scale models. From the perspective of structural optimization, when the cone angle of ferrule is increased from 15° to 17°, the axial range of the sealing contact area is expanded by 0.03–0.06 mm, and the sealing area is increased by 14–28%. Increasing the cone angle of ferrule can improve the sealing contact area, but it is necessary to avoid pressure distribution degradation caused by excessive angle. The cone angle of the card sleeve should be 16°. In order to achieve a good sealing state of pipeline fittings, the yield strength of ferrule should be lower than the yield strength of pipeline. When the yield strength of ferrule is 90% to 95% of the yield strength of pipeline, a balance between uniform distribution of sealing contact pressure and effective sealing area can be achieved. This article clarifies the key influencing laws of the matching between the cone angle of ferrule and the yield strength of the material, providing data and theoretical basis for multi-objective optimization design of aviation pipeline fittings.